Learning to communicate science increases students’ motivation. “The Scientific Conference”, a didactic proposal in Secondary Education. - Gollerizo-Fernández, Adrián; Clemente-Gallardo, María (Revista Electrónica Educare, 2019)
In this paper, we describe the “Scientific conference,” a didactic proposal consisting in organizing a scientific congress by secondary school students. The students work in a research project about topics that delve into some contents of the official curriculum with the purpose of communicating the results of this project the day of the celebration of the congress. This proposal will allow the development of several competences at the same time, in particular, the linguistic competence. The purpose of this study is to analyze if participation in this experience increases students’ intrinsic motivation towards Physics and Chemistry subjects. The “Scientific conference” has been put into practice with a group of students of 4th ESO at a public secondary school in Getafe (Madrid). It was a quantitative-approach study, by means of a pretest-posttest design with one experimental group. An instrument that enables gathering data related to students’ intrinsic motivation towards Physics and Chemistry subjects has been used. The results of the study showed that the didactic proposal improved students’ levels of intrinsic motivation and, in particular, their levels of interest and enjoyment of the subject. These results point out that this kind of proposal can be a good starting point for the improvement of students’ motivation towards science learning.